Comparative Analysis on the Rule-based Control Strategy of Two Typical Hybrid Electric Vehicle Powertrain. (December 2016) - Wu, Jingda; Peng, Jiankun; He, Hongwen; Luo, Jiayi
Abstract: Series-Parallel Hybrid ElectricVehicle (HEV) has well applied in practice due to its significant advantages, this paper aimed at two different kind of Series-Parallel HEV configurations: Power Split and Mode Switching configuration, comparing their control strategies, set model and simulate to verify, obtain features and applications of two configurations. The simulation results show that the power split configuration does better in protecting battery and reducing urban fuel consumption, while mode switching configuration has simpler structure.